Socioeconomy and perspectives of açaizeiro production systems in the Municipality of Abaetetuba (PA), brazilian Amazon (Research, Society and Development, 2021)
In this work, there is an attempt to answer if the system of extractive production and management of “açaí” (Euterpe oleracea Mart.) could maintain socioeconomically sustainable. With this purpose, it was raised the socioeconomic and productive profile of native açaizal extractivists and managers in Uruá and Paruru islands and in the emerging system of planting in terra firme areas of Abaetetuba (PA) municipality, one of the main national açaí producers. One hundred (100) semi-structured questionnaires were applied to the açaí producing families in these communities on both islands and seven in terra firme areas. In this way, the socioeconomic characterization of the producing families, the production systems adopted and the conditions of some public policies, such as credit and technical assistance were observed to stimulate their development and sustainability. The results indicated that, due to the increasing demand for the fruit, the producers were able to generate an additional income, raising their living standard. However, problems related to productive infrastructure and the need to expand the supply of açaí, on a rational and sustainable basis persist, to meet the market demand that has expanded strongly both at the regional and national levels, as in various market niches in some countries. The açaizeiro (Euterpe oleracea Mart.) cultivation in areas already altered in the economy of Pará, and with appropriate technology, while consolidating an important economic activity at the local level, including involving small producers, can help to ensure the conservation of Amazon native areas.